2016
DOI: 10.1177/1534735415617014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Endurance Exercise on Doxorubicin-Induced Thymic Damage

Abstract: The use of prior exercise training has shown promise in minimizing doxorubicin (DOX)-induced physical impairments. The purpose of this study was to compare changes in thymus mass, thymocyte (T-cell) number, and tissue peroxidation following chronic endurance exercise and DOX treatment in the rat. The thymus mass, number of viable T-cells, and levels of malondialdehyde and 4-hydroxyalkenals (MDA+4-HAE) were compared 3 days post-injection between rats assigned to the following treatment conditions: (a) 10 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…While molecular and cellular changes have been described for cardiac tissue following DOX treatment, the changes leading to the pronounced thymic [ 64 Cu]­Cu-RGD uptake are less known. ,,, One study has described thymic involution and reduced T lymphocyte counts after exposure to DOX . The same study found normal macrophage counts and a slightly reduced number of dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…While molecular and cellular changes have been described for cardiac tissue following DOX treatment, the changes leading to the pronounced thymic [ 64 Cu]­Cu-RGD uptake are less known. ,,, One study has described thymic involution and reduced T lymphocyte counts after exposure to DOX . The same study found normal macrophage counts and a slightly reduced number of dendritic cells.…”
Section: Discussionmentioning
confidence: 99%